ANALYSIS OF THE IMPLEMENTATION OF OCCUATIONAL SAFETY AND HEALTH AT THE MANISAK COMMUNITY HEALTH CENTER MANDAILING NATAL REGENCY 2024 - Herlina J. EL-Matury; Paradiba Sandi (Jurnal Inovasi Kesehatan Masyarakat, 2026)
Occupational Safety and Health (K3) is an important aspect in health care facilities such as Community Health Centers, which have high potential risks to the health of workers, patients, and visitors. Based on the results of an initial survey at the Manisak Community Health Center, various problems were found related to the implementation of K3. This indicates the need for evaluation and analysis of the implementation of K3 at the Community Health Center. This study aims to analyze the implementation of Occupational Safety and Health at the Manisak Community Health Center, Ranto Baek District, Mandailing Natal Regency in 2024. This study uses a qualitative approach with a case study approach. The informants in this study consisted of health workers and related parties at the Manisak Community Health Center. Data collection was carried out through interviews, observations, and documentation studies. The data obtained were analyzed through interview results and adjusted to the policies in the Regulation of the Minister of Health Number 52 of 2018 concerning Occupational Safety and Health in Health Care Facilities. The results of the study indicate that the K3 policy has not been properly established because there is no K3 team or managerial decree and minimal understanding of leaders and staff about K3. K3 planning has also not been clearly documented and is not based on risk identification. The implementation of K3 standards has not been optimal because the planning is not yet clear. Monitoring and evaluation are only carried out if there is a problem, while performance review and improvement have never been carried out. Support from the Health Office is also still limited, both in terms of policies, facilities, and experts. In addition, K3 socialization is more often carried out for the general public, not specifically for health services at the Health Center.